Developing Speaking Skills through Interactive Storytelling in Language Teaching (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
Storytelling is one of humanity’s oldest forms of communication and has increasingly been recognized as a pedagogical tool in second and foreign language classrooms. When applied interactively—engaging students in the co-construction, improvisation, or digital presentation of stories—storytelling can be a powerful means to develop learners’ speaking proficiency. This article explores the theoretical foundations of interactive storytelling in language teaching and examines its specific impact on fluency, accuracy, pronunciation, and learner confidence. Drawing on sociocultural theory, narrative theory, and the Output Hypothesis, the article presents classroom models of interactive storytelling, including collaborative story creation, digital storytelling, and role-based improvisation. Empirical studies from various contexts are reviewed to highlight measurable improvements in oral skills. Challenges related to assessment, learner resistance, and cultural adaptation are also discussed. Overall, the article supports storytelling as a flexible, engaging, and research-supported strategy to build oral competence in language learners.